Absolutely minimum attaining Toeplitz and absolutely norm attaining Hankel operators - Ramesh, Golla; Sequeira, Shanola S. (Comptes Rendus. Mathématique, 2023)
In this article, we completely characterize absolutely norm attaining Hankel operators and absolutely minimum attaining Toeplitz operators. We also improve [19, Theorem 2.1], by characterizing the absolutely norm attaining Toeplitz operator $T_φ $ in terms of the symbol $φ \in L^∞ $.